Evaluation Of The Masonry Concrete Arch Structural Response And Prediction Of Crack Using Non-Contact And Contact Technique - Salleh, Nadia Syahiera (Universiti Sains Malaysia, 2022)
Concrete cracking is unpredictable and difficult to predict due to the nonlinear characteristics of concrete. For this reason, studies on the structural response of masonry concrete arches are very essential. The study aims to evaluate the response of the arch structure under loading using non-contact and contact techniques and predict the crack path. Non-contact and contact device analysis techniques are used to track the structure's condition, with strain distribution on the concrete surface being measured with GOM Software. It is possible to predict the path of cracks in a sample using GOM software's image analysis of the strain field. Using a smartphone camera, a drone, and the DEMEC Gauge, this study analyses how non-contact and contact techniques can be used to predict structural cracks and evaluate the structural response of masonry concrete arches. A uniformly distributed load is applied at the midspan of the sample. For each load stage, the results of the non-contact and contact techniques were compared. For the upper horizontal, lower horizontal, and left vertical loading stages, the DEMEC gauge reading is taken. Data from DEMEC Gauge is compared with the values obtained from GOM Correlate. The results were analysed simultaneously using the contact method and the non-contact method. By measuring the strain on the sample surface, the smartphone was proven to be 50% more accurate than the drone in this experiment. The problem occurs when using a drone to evaluate strain using DIC. It is because drones generate a lot of movement caused by surrounding wind and also noise generated from its own blades during flight. As a result, the data in the drone video is more unpredictable. The structure's strain distribution, which shows where the highest strain is accumulated during the deformation process, was used to figure out where the crack path occurred.